Novel Nanocomposite Optical Plastics: Dispersion of Titanium in Polyacrylates. (11th April 2010) - Suri, Gunjan; Tyagi, Mukti; Seshadri, Geetha; Verma, Gurcharan Lal; Khandal, Rakesh Kumar
Abstract : Polyacrylates have become the preferred materials for optical applications replacing the conventionally used glass due to their superior optical clarity. The major disadvantage with polyacrylates is their low (1.40–1.50) refractive index besides their poor impact resistance. The improvements in refractive index as well as mechanical properties can be achieved by way of incorporation of metals or metal compounds in the matrix. A novel methodology for the incorporation of high refractive index metals into low refractive index polymeric materials to improve the refractive index and impact resistance of the latter has been developed. With the in-situ formation of nanoparticles of TiO 2, the refractive index of polyacrylates improved from 1.45 to 1.53 and the Abbe number increased from 40 to 57. One of the interesting dimension of this study pertains to the possibility of tailor-making of the two key optical properties of materials by way of varying the amount of TiO 2 being formed in-situ. Thermal stability and impact resistance of nano dispersed (4.3% by wt. of Ti) polyacrylates are found to be better than the neat polyacrylates. Moreover, TiO 2 -containing polyacrylate is of light weight. TEM, SEM, and IR analysis confirms the in-situ formation of nanoparticles of TiO 2 . Gamma irradiation has been used as an eco-friendly technique for polymerization. The developed compositions can be cast polymerized into clear and bubble free material for optical applications.